Building the digital archive of Hong Kong english learning: Methodology, challenges and reflection. (April 2017) - Lee, Klaudia Hiu Yen; Patkin, John G.
Abstract: This article reflects upon the processes and challenges of building a digital archive of English learning narratives, and engages with broader questions surrounding the collection and presentation of student narratives on an online platform. It also discusses the potential uses of the open-access archive in a global context. The archive hosts over 3000 student narratives collected in diverse leisure, educational, professional and cross-cultural settings in Hong Kong. The diverse learning strategies, approaches and challenges that students share thus provide a holistic record of second language learning practices in various contexts, thereby serving as a useful reference for educators, students and independent learners when they develop their own teaching and learning strategies and approaches.